Development of A Work-based Vestibule Training E-module For Accident Prevention at Malaysian Oil and Gas Drilling Industries: A Proposed Framework - Hassan, Razali; Asad, Muhammad Mujtaba; Sherwani, F. (International Journal of Sustainable Construction Engineering and Technology, 2020)
This article discusses the conceptual action plan and detailed methodology for the identification of potential hazard controls and the development of work integrated E-vestibule training module for safe onshore and offshore oil and gas drilling operation at Malaysian industries. According to the previous studies, there is a sheer industrial need of an effective work integrated vestibule training module for accident prevention at oil and gas drilling sites at Malaysian drilling domains. In this proposed study, 80 drilling crew will be randomly selected for quantitative research phase. Similarly, 03 safety experts will be purposively selected for qualitative research from each drilling domain. Whereas, for the identification of hazard controlling measures What-If analysis and thematic analysis approaches will be adopted. Furthermore, the open source vestibule training module will be developed by using ADDIE based on identified hazard controlling measures. However, the visual studio and MySQL software will use to develop the E-Module for drilling crew safety training. The proposed E-vestibule training module development framework will be used as an effective source for the elimination of life-threatening drilling hazards associated with its activities at oil and gas industries. Similarly, the proposed framework can also be implemented on other work-based learning training designs. Moreover, this proposed safety and health vestibule training module will be the first E- drilling safety module which covers all onshore and offshore drilling operation in Malaysian oil and gas extraction settings.